The management of university student research activity as process - Finalé de la Cruz, Leyda; Tarifa Lozano , Lourdes; Artola Pimentel, María de Lourdes (Atenas, 2016)
From the desk study, the evolution of the concept of student research activity is analyzed, determining the existence of a conceptual gap in their treatment as a process and the need to manage it from different university substantive processes in an interrelated is needed why management of student research activity is a constitutive process and its definition as well as the operationalization of the variable under study allowing evaluation features.